PENERAPAN MODEL PEMBELAJARAN INKUIRI BERBANTUAN MEDIA INTERNET DALAM MENINGKATKAN MOTIVASI BELAJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM SISWA KELAS VIII A DI SMPN 4 TELUK KUANTAN - Pricila Cindiana; Sopiatun Nahwiyah; Helbi Akbar (AL-HIKMAH (Jurnal Pendidikan dan Pendidikan Agama Islam), 2020)
This class action research was conducted in class VIII A of SMP Negeri 4 Kuantan Bay in the 2016/2017 school year from January to February 2018. The subjects of this study were students of class VIII A at SMP Negeri 4 Kuantan Bay as many as 21 people. One teacher of Islamic education, and 20 students with 7 men, and 13 women. This research is a classroom action research (CAR). This study aims to improve students' motivation to learn Islamic religious education by using the inquiry learning model assisted by internet media. Student learning motivation before PTK is 30%. Motivation of students in the first cycle is 50%, in the second cycle is 70%, and in the third cycle is 90%. This research proves that the application of inquiry learning model assisted by internet media can increase learning motivation in Islamic religious education subjects for Grade VIII A students at SMP Negeri 4 Teluk Kuantan.